Social Entrepreneurial Motivation during the Covid-19 Pandemic: A Literature Study - Muhammad Nazif A’zam; Jihan Salsa Dila; Yollawati Arifi; Aftina Nurul Husna (Urecol Journal. Part H: Social, Art, and Humanities, 2021)
Social entrepreneurship is an activity to identify social problems and use entrepreneurial principles to create efforts to achieve change in social interests. In running a business, motivation is needed to keep doing what has been established. This study aims to gather information through literature studies regarding how social entrepreneurs are able to survive running their economies during a pandemic. This research method uses a systematic literature review by summarizing the results of previous studies. Based on this study, it was found that there are five aspects that influence the motivation of social entrepreneurship, including: personal fulfillment, helping society, non-monetary focus, achieving orientation, and closeness to social problems.